Evaluation of peanut genotypes for resistance to Tomato spotted wilt virus by mechanical and thrips inoculation - Nascimento, Luciana Cordeiro do; Pensuk, Viboon; Costa, Nivânia Pereira da; Filho, Francisco Miguel de Assis; Pio-Ribeiro, Gilvan; Deom, Carl Michael; Sherwood, John (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the reactions of three peanut breeding lines (IC-10, IC-34, and ICGV 86388) to Tomato spotted wilt virus (TSWV) by mechanical and thrips inoculation, under greenhouse conditions, and compare them to the reactions of cultivars SunOleic, Georgia Green, and the breeding line C11-2-39. TSWV infection by mechanical inoculation was visually assessed using an index ranging from 0 (no symptoms) to 4 (apical death). Enzyme-linked immunosorbent assay was used to confirm TSWV infection from both mechanical and thrips inoculations. IC-10, IC-34, ICGV 86388, and C11-2-39 were more resistant than the cultivars SunOleic and Georgia Green based on mechanical inoculation. Upon thrips inoculation only IC-34 and ICGV-86388 were infected by TSWV, as demonstrated by reverse transcription polymerase chain reaction (RT-PCR), although no symptoms of infection were observed. The peanut breeding lines IC-10, IC-34, and ICGV 86388 show higher level of resistance to TSWV than cultivar Georgia Green considered a standard for TSWV resistance.